Keterlibatan Mahasiswa Kuliah Kerja Nyata dalama Kegiatan Sosial, Keagamaan, dan Lingkungan Masyarakat di Jorong Bawah Gunung - Ade Huzaini Andra; Farhan Hayyi Nanda; Harya Suhandika; Nabil Alif; Nurul Fadilla; Wilfrida Sahartini Lase; Yuliandri Akmal (CV. ITTC INDONESIA, 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student community engagement that places students directly within society to understand local social conditions while contributing to community development. The KKN program implemented in Jorong Bawah Gunung, Nagari Batu Bajanjang, Lembang Jaya District, Solok Regency, focused on student participation in social, religious, and environmental activities. The main activities carried out included the construction of informational signboards, such as direction signs to the mosque, the “ikan larangan” (protected fish area), and the route to Mount Talang. The implementation process began with field observation and identification of community needs, followed by discussions with local authorities and residents. The program was then planned and executed in collaboration with the community through a participatory approach. The results indicate that the installation of signboards improved access to location information for both residents and visitors, making it easier to identify important places within the area. Furthermore, the program fostered stronger social interaction between students and the community through involvement in various social and religious activities. This KKN program did not only focus on physical outputs in the form of signboards but also emphasized community engagement and collaboration throughout the process. This experience provided valuable insight for students into their role within society and demonstrated how simple, well-planned interventions can deliver meaningful benefits to the local environment.